7+v(0.875s+-0.375)=6+v

Simple and best practice solution for 7+v(0.875s+-0.375)=6+v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+v(0.875s+-0.375)=6+v equation:


Simplifying
7 + v(0.875s + -0.375) = 6 + v

Reorder the terms:
7 + v(-0.375 + 0.875s) = 6 + v
7 + (-0.375 * v + 0.875s * v) = 6 + v

Reorder the terms:
7 + (0.875sv + -0.375v) = 6 + v
7 + (0.875sv + -0.375v) = 6 + v

Solving
7 + 0.875sv + -0.375v = 6 + v

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + 0.875sv + -7 + -0.375v = 6 + -7 + v

Reorder the terms:
7 + -7 + 0.875sv + -0.375v = 6 + -7 + v

Combine like terms: 7 + -7 = 0
0 + 0.875sv + -0.375v = 6 + -7 + v
0.875sv + -0.375v = 6 + -7 + v

Combine like terms: 6 + -7 = -1
0.875sv + -0.375v = -1 + v

Add '0.375v' to each side of the equation.
0.875sv + -0.375v + 0.375v = -1 + v + 0.375v

Combine like terms: -0.375v + 0.375v = 0.000
0.875sv + 0.000 = -1 + v + 0.375v
0.875sv = -1 + v + 0.375v

Combine like terms: v + 0.375v = 1.375v
0.875sv = -1 + 1.375v

Divide each side by '0.875v'.
s = -1.142857143v-1 + 1.571428571

Simplifying
s = -1.142857143v-1 + 1.571428571

Reorder the terms:
s = 1.571428571 + -1.142857143v-1

See similar equations:

| 3t^2+6t+2=26 | | -6z+14=-7z | | (x^2-6x+2)(x^2+3x+2)=0 | | 2x-5=7-2x | | 3t^2+6t+2=0 | | t=16t^2+2704 | | 5m=2m-9 | | 5u^2-90=0 | | 12x-9=6x+4 | | 0=7m | | 0.9x+0.2x-6=5 | | (x-1)5=(x-2)3 | | 2x^2-27x-80=0 | | 88=125-(-x) | | 9y=-270 | | 1.8w+2.8=2.5w+2.1 | | 42x=x+2 | | X-(1/3x)=800 | | 2w-5=3(1-2w) | | X+(2x-1)=23 | | 24=3/8x | | 180=-6x | | on(2-3x)=8 | | -x-4=15 | | (x^2-2x+1)(x^2+5x+6)=0 | | -6x+5=-4x-19 | | 5x^3=120 | | .57x=18 | | (-5x^2)-(-9x^2)= | | 3x+3x+-1=4x+9 | | -4(m+6)=.8 | | p/9-5=2 |

Equations solver categories